BUDIKDAMBER: Realisasi Konsep Urban Farming di Kelurahan Simpang Tiga.docx - Fara, Lulu; Yafi Fadhillah, Muhammad; Fadhilah, W. Dea; Izzati, Kalonika; Wahyuni, Nita; Triyuliani Hasdania, Nabila; Agustina, Alda; Librina Suhardi, Dwi; Nur Yasin, Annisa; Adrian Sembiring Pelawi, Amos; Saleh Basobih, Fadel (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Abstract—The increasing population growth in Pekanbaru City from year to year has caused the shift of land functions to be residential areas or other functions. This ha is intended to accommodate the increasing population of the community, so that in every corner of the city in Pekanbaru City, there are now many residential areas. Along with the development of technology, it is necessary to anticipate a decrease in aquaculture production due to reduced cultivation land and decreased water quality. Therefore, service students carry out budikdamber activities which can be a solution to limited land and can also be used as a forum for their own entrepreneurship. In this paper, we will discuss how to realize the concept of Budikdamber in Simpang Tiga Village. It is recommended that activities like this can be carried out continuously so that the targets are extended to other communities.